(untitled) (Recoletos Multidisciplinary Research Journal, 2025)
Background: A prescriptive argument holds that the focusing modifier (FM) only should be pre-adjacent to its focus. This study investigates the non-prescriptive usage of only in Philippine English (PhE). It analyzes such an FM in PhE writing, following Huddleston and Pullum?s types of only-construction. In light of Intercultural Rhetoric (IR) research, it also compares the PhE result with the parent variety, American English (AmE). Methods: This study is a corpus-based investigation, using corpora of PhE and AmE. The analysis is done through a concordance tool to reveal the usage of the FM only. Intercoder agreement is employed for the reliability of the findings. Results: Both Englishes dominantly use only within a verb phrase construction, while variations are seen in focus-construction types. This study shows that using the FM only, PhE has not deviated much from AmE, so there is little cultural influence in both Englishes. This suggests a shared grammatical intuition despite the differences in context. Conclusion: This study contributes to the literature on FMs about IR’s aim to consider similarities and differences in contrastive studies particularly in the context of the Philippines. It is recommended for future studies to use larger corpora of PhE.